2018
DOI: 10.1186/s13104-018-3893-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chemistry laboratory errors at St. Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia

Abstract: ObjectiveThis study was aimed to determine the magnitude of errors in clinical chemistry laboratory tests at different phases of the assay of clinical chemistry laboratory unit.ResultsFrom the total 1633 clinical chemistry laboratory tests done, overall, 541 (33.1%) errors occurred which accounts that 392 (72.3%), 45 (8.3%), and 104 (19.2%) were pre analytical, analytical and post analytical phases of errors, respectively. Incomplete clinical data of patient was observed on 1185 (72.6%) of CLL tests. Name, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
4
4
2
Order By: Relevance
“…Our study found a lower frequency of 6.2% IQC failure compared to the study conducted in Pakistan (32%), 46 but higher than the study conducted in Ethiopia (2.95%) 19 and India (0.6%). 47 The difference between findings may be due to variation in equipment and laboratory personnel performance, storage condition of QC materials, the reconstitution of lyophilized QC materials and availability of in-house mean/SD.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Our study found a lower frequency of 6.2% IQC failure compared to the study conducted in Pakistan (32%), 46 but higher than the study conducted in Ethiopia (2.95%) 19 and India (0.6%). 47 The difference between findings may be due to variation in equipment and laboratory personnel performance, storage condition of QC materials, the reconstitution of lyophilized QC materials and availability of in-house mean/SD.…”
Section: Discussioncontrasting
confidence: 81%
“…The current study found that the prevalence of errors in the TTP was 15.3%. This finding was lower than the study conducted in Addis Ababa, Ethiopia (33.1%) 19 but higher than the study conducted in Saudi Arabia (4.35%) 42 and Ghana (4.7%). 33 This may be due to difference in the infrastructure of the laboratory, regular monitoring and evaluation, availability of functional LIS, competency of laboratory staffs, in-house mean/SD, variation in the study designs, operationalization of variables and QIs.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations